Intelligibility in the early language contact in Danelaw revisited - Katarzyna Sówka-Pietraszewska; Gabriela Grelowska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The problem of intelligibility between Anglo-Saxons and Scandinavians in Danelaw has been a matter of dispute for over a century now. Two perspectives of looking at this issue have been proposed. One group of scholars claim that, due to a fair number of similarities in the lexis and grammar of the languages, the level of mutual intelligibility was high. The other party strongly objects to the view of commonalities and mutual comprehension. Instead, they argue for the idea of emerging bilingualism in Danelaw. This paper aims to adduce arguments to the claim of mutual intelligibility proposed by Townend (2002), among others. We provide an insightful etymological account of meticulously collected parallel words in the analysed languages. The search for the common ancestry of lexical roots is enhanced by the study of cultural context. Moreover, a comparative analysis of syntax, morphology, and pronunciation is also provided. The proposed complex analysis leads to the conclusion that the level of mutual intelligibility between the Old English speakers and Norsemen was high.